The Application of Principle of Mistake as Legal Liability on the Criminal Theft - Muhammad Heriyansyah; Amin Purnawan; Achmad Sulchan (Law Development Journal, 2022)
This study aims to determine the application of the principle of error as legal responsibility for the crime of theft in the Tanjungpinang District Court Decision. By using a normative juridical approach that is descriptive analytical. The results of the study showed that the application of the principle of guilt as absolute liability in criminal law as the basis for imposing a crime, the defendant was proven unlawfully against the law in violating the material elements of Article 363 paragraph (1) 3 and 4 of the Criminal Code. So the form of error committed by the defendant if qualified is intentional. Deliberately can mean deliberately to do something and deliberately not to do something that should be done.